Rare‐Earth Metal Ions Doped Graphene Quantum Dots for Near‐IR In Vitro/In Vivo/Ex Vivo Imaging Applications. Issue 21 (16th August 2020) - Hasan, Md. Tanvir; Gonzalez‐Rodriguez, Roberto; Lin, Ching‐Wei; Campbell, Elizabeth; Vasireddy, Satvik; Tsedev, Uyanga; Belcher, Angela M.; Naumov, Anton V.
Abstract: Near‐infrared (NIR) emitting biocompatible nanomaterials are desired in biotechnology as higher penetration depth fluorescence imaging probes. In this work, novel NIR‐emissive Nd 3+ ‐doped or Tm 3+ ‐doped biocompatible graphene quantum dots (GQDs) are developed via scalable, single‐step bottom‐up synthesis. Water‐soluble Nd‐GQDs/Tm‐GQDs with average diameters of 5.6–8.2 nm possess crystalline graphene lattice with < 1 atomic percent of Nd/Tm and exhibit NIR fluorescence at ≈ 1060/≈ 925 nm attributed to the intrinsic transitions of Nd 3+ /Tm 3+ . High biocompatibility with > 80% cell viability at 1 mg mL −1 for Nd‐GQDs and 0.25 mg mL −1 for Tm‐GQDs makes them well‐suited for bioimaging. In vitro, both GQD types exhibit efficient internalization with their intracellular emission maximized at 6 h. The pH‐dependence of this emission can serve as plethora of diagnostic applications. GQDs enable in vivo NIR imaging in live sedated NCr nude mice with IV administration: their NIR emission maximized at 6 h post‐injection is primarily detected in intestine, kidneys, liver, and spleen, however, diminishing to none at 48 h. Ex vivo organ/slice imaging shows significant Tm‐GQD fluorescence signatures in the aforementioned organs/slices. This capability of NIR fluorescence imaging in cells, tissues, and real‐time detection in live animals makes biocompatible rare‐earth metal‐doped GQDs an attractive new candidate for in vitro/in vivo/ex vivo theranostics. Abstract : A scalable/eco‐friendly/cost‐effective microwave‐driven hydrothermal route is utilized to develop Nd 3+ ‐doped and Tm 3+ ‐doped graphene quantum dots exhibiting near‐infrared (NIR) fluorescence at ≈1060 and 925 nm, respectively, with NIR excitation assigned to the intrinsic transitions of Nd 3+ /Tm 3+ dopants. These biocompatible quantum dots are further utilized successfully for in vitro, in vivo, and ex vivo bioimaging applications.